Pengaruh Tangibility, Growth Opportunity, Size, Profitability, dan Risk Terhadap Struktur Modal: dalam Perspektif Pecking Order Theory pada Perusahaan Automotive and Allied Products di BEI - Nuarsari, Devi Wahyu (BISMA (Bisnis dan Manajemen), 2018)
This research aims to test influence of tangibility, growth opportuity, size, profitability, and risk on the capital structure. This research is conducted on Automotive and Allied Products companies at BEI period 2004-2009, that still listed in the Indonesian Capital Market. The result of the test concluded that tangibility and size has a positive influence to the capital structure, but profitability dan risk has a negative influence to the capital structure, and growth opportunity has a negative influence to the capital structure but not significant.